Le tolérantisme musical - Stefanija, Leon (Muzikološki zbornik, 2007)
The essay is conceived of as a set of comments on Le tolérantisme musical by Antoine Bemetzrieder. His text, published in 1779, discusses the three main European musical cultures and the hierarchy among them (Italian hegemony over German and French music). While reflecting on the reasons for this, Bemetzrieder reveals the sociological coordinates of identifying the national imprint in the music of the 18th century (offering a pragmatic solution to the "right solution" regarding Italian hegemony: the establishment the French National Opera House) while at the same time offering epistemological premisesthat deserve contemporary musicological attention. The comments added to the translation of Bemetzrieder's text relate to epistemological issues contained within it, leaving aside the historically important content so crucial for the text.
Keywords: anthropology; antropologija; Bemetzrieder, Antoine, 1739-1808; glasba; music; sociologija; sociology; spoznavoslovje